Anthropogenic Infrastructures Shape Brown Bear Movements in Human-Modified Landscapes - García-Sánchez, Pino; Penteriani, Vincenzo; Delgado, María del Mar; Falcinelli, Daniele; Fedorca, Ancuta; Gentle, Louise K.; Kojola, Ilpo; Heikkinen, Samuli; Find'o, Slavomír; Skuban, Michaela; Fedorca, Mihai; Ionescu, Ovidiu; et al. (Wiley-Blackwell, 2026)
In Europe, large carnivore populations have faced a history of persecution and habitat alteration, varying in magnitude across their distribution. Individual animals have developed diverse adaptations to these anthropogenic activities, in most cases to avoid them but in some cases to exploit novel resources in the human-modified environments they inhabit. Here, we used long-term GPS-telemetry data from 108 brown bears Ursus arctos collared across three European countries – Finland, Slovakia and Romania—to assess whether the behavioural movement patterns of brown bears are consistent across their range or vary regionally in response to local environmental and anthropogenic influences. We calculated speed, movement direction and daily displacement, and used mixed-effects models to analyse whether human infrastructure affected brown bear movement behaviour across the study areas. To examine whether the impact of these features varied by study area, and to capture contextual differences that may have affected the movement patterns of bears, we included interactions between environmental predictors and area in the regression models. Our results showed that Finnish bears exhibited consistently higher movement speeds and longer daily displacements than Slovak and Romanian bears, regardless of the proximity to roads, railways, or human settlements. In addition, in proximity to transport infrastructures, Finnish and Slovak bears increased speed, directionality and distance travelled whereas Romanian bears showed the opposite pattern. Conversely, near human settlements, Romanian bears showed higher speeds and less tortuous movements, whereas Finnish and Slovak bears reduced their speed and daily displacements. These contrasting responses suggest that bear movements in multi-use, human-modified landscapes are shaped by complex interactions between animal needs and local environmental conditions.
Keywords: behavioural plasticity; human infrastructure; large carnivores; movement ecology; telemetry; Ursus arctos